1984
DOI: 10.1111/j.1747-4469.1984.tb00019.x
|View full text |Cite
|
Sign up to set email alerts
|

Police Accountability and the Media

Abstract: This article explores First Amendment theory and the role of the media in generating police accountability through public understanding of police organizations. We argue that free speech theory can and should look beyond “abridgment” issues and raise questions about the civic responsibility of the press to inform the public about key governmental institutions. The media's concern with crime news, we found, vastly overshadows its coverage of the police us a complex, in-teresting, and expensive governmental agen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…There is some debate about who benefits most from this relationship, although most scholars conclude that the relationship is not contentious (Chermak, 1995a(Chermak, , 1997Chibnall, 1977;Crandon, 1995;Crandon & Dunne, 1997;Fishman, 1980;Grabosky & Wilson, 1989;Hall et al, 1978;Hatty, 1991;Kasinsky, 1994;Skolnick & McCoy, 1985;Surette, 2001). For example, Skolnick and McCoy (1985) concluded that there was no overt hostility between the police and the media, and Hatty (1991, p. 172) concluded, bThis mutually beneficial arrangement promotes the legitimacy of the police and the media.Q It would be a stretch to conclude that the relationship between the two organizations is always amicable.…”
Section: Previous Research On Public Information Officersmentioning
confidence: 96%
See 2 more Smart Citations
“…There is some debate about who benefits most from this relationship, although most scholars conclude that the relationship is not contentious (Chermak, 1995a(Chermak, , 1997Chibnall, 1977;Crandon, 1995;Crandon & Dunne, 1997;Fishman, 1980;Grabosky & Wilson, 1989;Hall et al, 1978;Hatty, 1991;Kasinsky, 1994;Skolnick & McCoy, 1985;Surette, 2001). For example, Skolnick and McCoy (1985) concluded that there was no overt hostility between the police and the media, and Hatty (1991, p. 172) concluded, bThis mutually beneficial arrangement promotes the legitimacy of the police and the media.Q It would be a stretch to conclude that the relationship between the two organizations is always amicable.…”
Section: Previous Research On Public Information Officersmentioning
confidence: 96%
“…For example, Skolnick and McCoy (1985) concluded that there was no overt hostility between the police and the media, and Hatty (1991, p. 172) concluded, bThis mutually beneficial arrangement promotes the legitimacy of the police and the media.Q It would be a stretch to conclude that the relationship between the two organizations is always amicable. The relationship is constantly evolving as police are faced with celebrated cases, corruption scandals, and leadership turnover.…”
Section: Previous Research On Public Information Officersmentioning
confidence: 96%
See 1 more Smart Citation
“…This is also supported by the literature (e.g., McDonald, 1985). The prosecuting attorney has the authority to review all arrest warrants prior to court actions and has overall supervision of cases prepared by the police (Moore, Thacher, Dodge, & Moore, 2002;Skolnick & McCoy, 1985). In the case study city, instead of considering only the "probable cause" standard at the time an arrest warrant is sought, the judge, magistrate, or prosecutor were using a "beyond a reasonable doubt" standard for evidence necessary for conviction.…”
Section: Courts and Prosecuting Attorney Impactmentioning
confidence: 99%
“…Second, we examine the types of sources that news reporters have relied on and how they have used them in stories about consolidation. Prior research examining the representation of crime, policing, and other criminal justice issues highlights how sources are concerned about the public representation of social problems and issues, invest considerable resources to develop strategies that result in issues being presented in a positive way, and are well positioned to frame issues in a way that is consistent with their preferred understandings of them (Chermak & Weiss, 2005; Skolnick & McCoy, 1985; Surette & Richard, 1995). Consolidation is potentially a very contentious issue impacting communities in different ways, and thus multiple interest groups have a stake in the presentation of this issue in the news media.…”
Section: Introductionmentioning
confidence: 99%